2013
DOI: 10.1002/lary.24094
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of pressure ulcers after pediatric tracheotomy using a Mepilex Ag dressing

Abstract: The use of Mepilex Ag after pediatric tracheotomy reduces the occurrence of postoperative peristomal pressure ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 20 publications
2
61
0
Order By: Relevance
“…The findings of this small study indicated that the dressing simultaneously resolved localised infection and addressed the issues of pain and trauma in the treatment of DFUs (Table 7). 87 Two studies highlighted the use of Mepilex Ag in preventing complications of tracheostomy care in vulnerable populations, paediatric patients 90 and (in a poster) obese individuals in intensive care. 91 In a retrospective case study review, Kuo et al 90 identified 134 paediatric patients who underwent a tracheostomy between June 2005 and June 2011.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this small study indicated that the dressing simultaneously resolved localised infection and addressed the issues of pain and trauma in the treatment of DFUs (Table 7). 87 Two studies highlighted the use of Mepilex Ag in preventing complications of tracheostomy care in vulnerable populations, paediatric patients 90 and (in a poster) obese individuals in intensive care. 91 In a retrospective case study review, Kuo et al 90 identified 134 paediatric patients who underwent a tracheostomy between June 2005 and June 2011.…”
Section: Resultsmentioning
confidence: 99%
“…87 Two studies highlighted the use of Mepilex Ag in preventing complications of tracheostomy care in vulnerable populations, paediatric patients 90 and (in a poster) obese individuals in intensive care. 91 In a retrospective case study review, Kuo et al 90 identified 134 paediatric patients who underwent a tracheostomy between June 2005 and June 2011. Before February 2010, dressings were not applied at the end of the tracheostomy procedure in almost 70% patients (n=93); the remainder (n=41) had Mepilex Ag applied under newly applied tracheostomy tubes.…”
Section: Resultsmentioning
confidence: 99%
“…Bundling the most common devices (eg, NIPPV masks) with preventive dressings will aid in getting the dressing on at the time of placement without delaying the process. [22][23][24] Examining the skin is a crucial component of prevention, for example, changing the location or repositioning the device at routine intervals if possible. In one large study, >74% of MDR PrUs were not identified until they were stage 3, 4, or unstageable.…”
Section: Experience In Clinical Practicementioning
confidence: 99%
“…In 2012-13, a western US hospital had reduced the incidence of traditional PrUs on the sacrum, coccyx, and heel from 5.9% to 0.1% using an evidence-based (EB) SKIN (Support surface, Keep the patient moving, Incontinence management, Nutritional support) bundle 22 including a five-layered foambordered dressing (Mepilex® Border Sacrum by Mölnlycke). Thus, the number of MDR PrUs became much more transparent.…”
Section: Experience In Clinical Practicementioning
confidence: 99%
“…Respiratory device-related hospital-acquired pressure ulcers slightly decreased in frequency following adoption of the initiative [22]. A retrospective study comparing the rate of peristomal skin breakdown at first tracheostomy change before and after initiation of a standard practice of placing a silver-impregnated foam dressing (Mepilex Ag, Oakville, Ontario, Canada underneath new tracheostomy tubes and ties showed a decrease in skin break from 11.8% to 0% [23]. …”
mentioning
confidence: 99%